2021
DOI: 10.1007/s12072-021-10182-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and economic burden of nonalcoholic steatohepatitis in Saudi Arabia, United Arab Emirates and Kuwait

Abstract: Background and aims The Middle East (ME) has a high prevalence of nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH), driven by obesity and type-2 diabetes mellitus (T2DM). Studies in Saudi Arabia (KSA) and United Arab Emirates (UAE) predict an escalating impact of NAFLD/NASH, particularly advanced fibrosis due to NASH (AF-NASH), increasing cases of cirrhosis, liver cancer and death. The scale of this burden in other ME countries is unknown with no reports of NAFLD/N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…In SA, the prevalence of overweight (70%), obesity (35%), and physical inactivity (35%) are higher in adults, with a high prevalence of T2DM [ 35 – 38 ]. Undoubtedly, NASH is a consequence of this quadruple-prong epidemic (i.e., syndemic) in SA [ 39 ]. Other potential consequences can include increases in the number of donors with pre-obesity and obesity, which negatively impacts donor complications and LT outcomes for recipients.…”
Section: Discussionmentioning
confidence: 99%
“…In SA, the prevalence of overweight (70%), obesity (35%), and physical inactivity (35%) are higher in adults, with a high prevalence of T2DM [ 35 – 38 ]. Undoubtedly, NASH is a consequence of this quadruple-prong epidemic (i.e., syndemic) in SA [ 39 ]. Other potential consequences can include increases in the number of donors with pre-obesity and obesity, which negatively impacts donor complications and LT outcomes for recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 28 articles included in this review, 13 were burden-of-disease studies that did not investigate a particular intervention, of which 6 reported both economic and clinical burden of disease, 19,[27][28][29][30][31] and 7 focused solely on clinical burden of disease. 3,[21][22][23][24][25][26] Eight articles primarily analyzed treatment interventions, 20,[32][33][34][35][36][37][38] of which 1 analyzed a hypothetical treatment.…”
Section: Summary Of Studiesmentioning
confidence: 99%
“…In 8 studies, NASH was considered a disease progression from NAFLD and only NASH patients could subsequently develop fibrosis. 27,29,31,39,42,43,45 Tapper et al 44 modeled NAFLD and NASH as 2 separate health states and NAFLD patients could transition to advanced fibrosis without first developing NASH. A similar approach was taken in 7 studies based on the same model.…”
Section: Nonalcoholic Fatty Liver Disease-nonalcoholic Steatohepatitismentioning
confidence: 99%
“…Recent figures suggest that more than 50% of the Omani population is overweight, and 30% have a body mass index (BMI) of more than 30% [ 15 ]. Neighboring countries such as the United Arab Emirates (UAE) and Saudi Arabia which are also struggling with a high burden of obesity have reported a NAFLD prevalence of 25% [ 16 , 17 ], posing a significant economic burden [ 18 ]. A recent analysis of Global Burden of Disease data noted the increasing prevalence of NAFLD across all regions of the world from 1990 to 2017 and pointed out Oman as the country with the maximum increase [ 19 ].…”
Section: Reviewmentioning
confidence: 99%